1977
DOI: 10.1111/j.1365-2141.1977.tb06833.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones Stimulate Erythropoiesis in Vitro

Abstract: Thyroid hormones have important effects on erythropoiesis in man and animals. We performed in vitro culture studies with murine and human bone marrow in order to define the interaction of these hormones with erythroid and granulocyte-monocyte progenitor cells. The methylcellulose clonogenic assay was used with the appropriate addition of erythropoietin or colony-stimulating activity. L-thyroxine, D-thyroxine and L-triiodothyronine potentiated erythropoientin-stimulated erythroid colony formation in concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
3

Year Published

1979
1979
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 22 publications
4
67
0
3
Order By: Relevance
“…Low temperature-induced erythropoiesis in mice (Fandrey et al, 1994). In connection with hematopoiesis, earlier studies demonstrated that TH stimulates the proliferation and differentiation of erythrocyte progenitors in vivo and in vitro (Golde et al, 1977;Dainiak et al, 1978). From these reports and our results, it would appear that TH triggers renal Epo gene expression after low temperature exposure, and erythropoiesis is subsequently enhanced by EPO.…”
Section: Discussionsupporting
confidence: 65%
“…Low temperature-induced erythropoiesis in mice (Fandrey et al, 1994). In connection with hematopoiesis, earlier studies demonstrated that TH stimulates the proliferation and differentiation of erythrocyte progenitors in vivo and in vitro (Golde et al, 1977;Dainiak et al, 1978). From these reports and our results, it would appear that TH triggers renal Epo gene expression after low temperature exposure, and erythropoiesis is subsequently enhanced by EPO.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, it has been postulated that the influence of THs on haematopoiesis involves an increased production of erythropoietin or haematopoietic factors by nonerythroid cells (10,11). However, a growing number of studies have demonstrated a direct role of THs in normal human and animal erythropoiesis (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Also iron clearance from the blood is reduced in hypothyroidism, suggesting reduced erythropoiesis. (15,17,18) The least common type of anaemia found in the present study was macrocytic anaemia (16%) and has been attributed to pernicious anaemia, decreased dietary intake and malabsorption of vit B12 and folic acid. Some studies have attributed much higher prevalence to this type of anaemia in hypothyroidism.…”
Section: Discussionmentioning
confidence: 86%